Criterion for Acceptable Bentonite Loss From a GCL Incorporated Into a Liner System. Issue 4 (1st January 2000) - Giroud, J.P.; Soderman, K.L.
Abstract : The following case is considered in the present paper: a geosynthetic clay liner (GCL) used in the composite primary liner of a double-lined landfill is overlain by a geomembrane and underlain by the secondary leachate collection layer, which consists of a geonet. If bentonite particles migrate downward out of the GCL, through the geotextile(s) that separate(s) the bentonite layer from the geonet, they penetrate into the secondary leachate collection layer. Depending on the amount of bentonite particles migrating from the GCL, these particles may decrease the hydraulic transmissivity of the secondary leachate collection layer. Also, the loss of bentonite particles from the GCL may decrease the performance of the composite liner. The present paper provides theoretical analyses of these detrimental effects of bentonite particle loss, which lead to an acceptance criterion that can be used to evaluate the results of tests performed to determine if the geotextile(s) that separate(s) the bentonite from the geonet is (are) suitable or if another (or additional) geotextile is necessary.